Achieving unity power factor at floating grid conditions in a cement plant in India-Case Study - Hasan Mydin J.; Umashankar S.; Sharma P.; Roshan R.; Ranganatha Chakravarthy H.S.; Ramachandaramurthy V.K. (IEEE Computer Society, 2023)
Active filters; Cement plants; Cements; Electric power factor; Electric power transmission networks; Internet of things; Outages; Reactive power; System stability; Waste heat; Waste heat utilization; Capacitor controls; Captive power plants; Cost optimization; floating grid; Grid conditions; Power factors; Unity power factor; Waste heat recovery systems; Electric power system control